Systemic Inflammatory Response and Severe Thrombocytopenia after Endovascular Thoracic Aortic Aneurysm Repair - Valentina Silvestrin; Stefano Bonvini; Michele Antonello; Franco Grego; Roberto Vettor; Marco Rossato (Case Reports in Medicine)
After Endovascular repair of thoracic aortic aneurysm, a systemic inflammatory response, named postimplantation syndrome, can develop. This syndrome is characterized by fever, leukocytosis, and elevated CRP plasma levels and its pathogenetic mechanisms are still unknown. Although this syndrome generally resolves within few days, some patients develop a persisting severe inflammatory reaction leading to mild or severe complications. Here we describe the case of a male patient who developed postimplantation inflammatory syndrome and severe thrombocytopenia after endovascular repair of thoracic aortic aneurysm. Treatment with prednisone (50 mg/bid) for two weeks did not improve the clinical and laboratory findings. We utilized danazol, a weak androgen that has been shown to be effective in the treatment of immune and idiopathic thrombocytopenic purpura, and after 12 days of treatment with danazol (200 mg/bid), the patient improved progressively and platelet number increased up to 53,000/μL. Patients undergoing endovascular repair of thoracic aortic aneurysm should be carefully monitored for the development of postimplantation syndrome. This clinical condition is relatively common after the endovascular repair of aortic aneurysm but is rarely observed after endovascular repair of thoracic aortic aneurysms. The different known therapeutical approaches are still empiric, with reported beneficial effects with the use of NSAID, corticosteroids, and danazol.